A Deleuzian Examination of Anorexia & Recovery: Opening up Possibilities for Conceptualizing Care - Gaudet, Sydney (Nursing philosophy, 2026)
Anorexia, a type of eating disorder, holds the highest mortality rate of all mental illnesses. Contemporary etiological consensus reflected in eating disorder literature views anorexia as the result of an interplay between biological, psychological, and social factors. However, the current organization of inpatient care fails to reflect such complexity and remains bound by biomedical knowledge regimes. Within these regimes, recovery is defined within a curative, disease-oriented framework, one that yields recovery rates of less than fifty percent. The following article serves as a meta-cognitive exercise, drawing on the work of French philosophers Gilles Deleuze and Félix Guattari. In particular, we use their ontology of immanence as a heuristic device to examine and challenge the hierarchical prioritization of biomedical ontological systems in how inpatient care and recovery for anorexia are conceptualized. As a result, we explore what an immanent conceptualization of inpatient care and recovery for anorexia might do to the organization of care and, by extension, the role of the nurse in eating disorder care.